2017
DOI: 10.1007/s11999-017-5246-4
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between Hemoglobin A1C and Deep Postoperative Infection After TKA?

Abstract: Level III, diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…It appears that higher cut‐offs are required for routine HbA 1C screening to have predictive value. A retrospective study found a large increase in prosthetic infection in patients with HbA 1C levels > 60.7 mmol/mol, while another found an association at levels > 63.9 mmol/mol . Given these retrospective studies are subject to bias, there is no high level evidence to support the routine screening of glycaemic control in TKA candidates.…”
Section: Optimising Pre‐operative Status To Maximise Recovery and Attmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that higher cut‐offs are required for routine HbA 1C screening to have predictive value. A retrospective study found a large increase in prosthetic infection in patients with HbA 1C levels > 60.7 mmol/mol, while another found an association at levels > 63.9 mmol/mol . Given these retrospective studies are subject to bias, there is no high level evidence to support the routine screening of glycaemic control in TKA candidates.…”
Section: Optimising Pre‐operative Status To Maximise Recovery and Attmentioning
confidence: 99%
“…A retrospective study found a large increase in prosthetic infection in patients with HbA 1C levels > 60.7 mmol/mol, 99 while another found an association at levels > 63.9 mmol/mol. 100 Given these retrospective studies are subject to bias, there is no high level evidence to support the routine screening of glycaemic control in TKA candidates. However, when HbA 1c control is also combined with other factors, including evidence (or lack) of patient self-monitoring, and the presence of diabetic comorbidities, there is a significantly increased risk of multiple adverse events.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Complications following THA have been identified as one of the leading cost drivers [19]. It has been well studied that patients with DM undergoing THA are at an increased risk of complications such as superficial site infections, periprosthetic joint infections, aseptic loosening, increased length of stay, and increased total hospital costs [8,11,12,20]. A positive correlation between rising HbA1c levels and increased risk of infection and cost has been shown [21].…”
Section: Discussionmentioning
confidence: 99%
“…An HbA1c level of 8 mg/dL has been shown to be associated with an increased risk of deep postoperative infections following THA [8,20]. Furthermore, HbA1c greater than 8 mg/dL correlates with an increased mortality [9].…”
Section: Discussionmentioning
confidence: 99%
“…A similar rationing of care is taking place regarding risk factors such as perioperative glucose control and tobacco use (Table 1). Preoperatively predicting perioperative glucose control remains challenging, however, and the validity of using hemoglobin A1c, which measures a collective 90‐days of serum glucose control, as a surrogate measure has recently been questioned 32–34 . Alternative tests such as perioperative serum glucose levels and fructosamine have been described as more sensitive measures of perioperative glucose control, and have demonstrated promise in preoperative screening for high‐risk patients 35,36 .…”
Section: New Advancements In Prevention Of Pjimentioning
confidence: 99%